2014
DOI: 10.1007/s10566-014-9288-4
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Symptoms Account for the Link between Reactive Aggression and Sleep Problems Among Latino Adolescents

Abstract: Background Sleep problems are common among adolescents and have a negative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
4
0
3
Order By: Relevance
“…Given the impulsive nature of both reactive aggression and delinquency, compared to the planful, deliberate behavior characteristic of proactive aggression [70–72], the current findings are not surprising. The limited research looking at aggression subtypes and delinquency in relation to sleep has found poor sleep to be associated with reactive but not proactive aggression [9, 71, 73] as well as with risk-taking delinquent behavior [74, 75]. The current study furthers this literature by looking at self-reported sleep quality and aggression subtypes in addition to delinquency in a sample of school-age youth.…”
Section: Discussionmentioning
confidence: 65%
“…Given the impulsive nature of both reactive aggression and delinquency, compared to the planful, deliberate behavior characteristic of proactive aggression [70–72], the current findings are not surprising. The limited research looking at aggression subtypes and delinquency in relation to sleep has found poor sleep to be associated with reactive but not proactive aggression [9, 71, 73] as well as with risk-taking delinquent behavior [74, 75]. The current study furthers this literature by looking at self-reported sleep quality and aggression subtypes in addition to delinquency in a sample of school-age youth.…”
Section: Discussionmentioning
confidence: 65%
“…In conditions with substance use disorders, others have shown that the total scores on the Barrat Impulsivity Scale (BIS) [11] [44] may predict violence [45]. Furthermore, anxiety symptoms seem to account for the link between reactive aggression and sleep problems among Latino adolescents [46]. Taken together, there is growing evidence for the existence of subgroups of aggression, which in some anxiety and impulsivity levels may identify at-risk behavior [27].…”
Section: Discussionmentioning
confidence: 99%
“…We are unable to offer an explanation for the lack of correlation between the inmates' symptoms scores for anxiety and scores for physical or verbal aggression in this study, but a lack of clinically significant anxiety cannot be ruled out. A relationship between anxiety and aggression may not necessarily be direct as indicated by studies showing that anxiety symptoms seem to account for the link between reactive aggression and sleep problems [46] and that anxiety may act as a mediator in some cases of physical aggression [14].…”
Section: Discussionmentioning
confidence: 99%
“…Además, el "jet lag social" se asociaría también a la agresión física, y las personas "orientadas hacia la tarde" ("eveningness") se percibían así mismas como más agresivas. Dos de los estudios correlacionales utilizaron como medida de la conducta agresiva la agresión reactiva (Vaughn et al, 2015;Fite et al, 2015). Ambos trabajos encontraron que el sueño deficiente y la agresión reactiva se hallarían significativamente asociados.…”
Section: Resultsunclassified